A voxel-based morphometric magnetic resonance imaging study of the brain detects age-related gray matter volume changes in healthy subjects of 21–45 years old. Issue 5 (October 2015) - Bourisly, Ali K; El-Beltagi, Ahmed; Cherian, Jigi; Gejo, Grace; Al-Jazzaf, Abrar; Ismail, Mohammad
Previous and more recent work of analyzing structural changes in the brain suggest that certain brain regions such as the frontal lobe are among the brain regions profoundly affected by the aging process across males and females. Also, a unified model of structural changes in a normally aging brain is still lacking. The present study investigated age-related structural brain changes in gray matter from young to early middle-age adulthood for males and females. Magnetic resonance images of 215 normal and healthy participants between the ages of 21–45 years were acquired. Changes in gray matter were assessed using voxel-based morphometry and gray matter volumetric analysis. The results showed significant decrease in gray matter volume between the youngest and oldest groups in the following brain regions: frontal, temporal, and parietal lobes. Grey matter loss in the frontal lobe was among the most widespread of all brain regions across the comparison groups that showed significant age-related changes in grey matter for both males and females. This work provides a unique pattern of age-related decline of normal and healthy adult males and females that can aid in the future development of a unified model of normal brain aging.